2018
DOI: 10.1007/s00344-018-9886-8
|View full text |Cite
|
Sign up to set email alerts
|

Phytohormone Priming: Regulator for Heavy Metal Stress in Plants

Abstract: Phytohormones act as chemical messengers and, under a complex regulation, allow plants to sustain biotic and abiotic stresses. Thus, phytohormones are known for their regulatory role in plant growth and development. Heavy metals (HMs) play an important role in metabolism and have roles in plant growth and development as micronutrients. However, at a level above threshold, these HMs act as contaminants and pose a worldwide environmental threat. Thus, finding eco-friendly and economical deliverables to tackle th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
144
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 344 publications
(145 citation statements)
references
References 116 publications
1
144
0
Order By: Relevance
“…Agricultural crops are under severe threats of various biotic and abiotic stresses, including salinity, drought and trace element stress (Adrees et al , Khan et al , Hussain et al , , b, Sytar et al ). Trace element stress is the most prevalent of these stresses, which not only inhibits crop growth by polluting agriculture soils, but also cause diseases in humans and animals (Hu et al , Song et al , Liu et al , Kataria et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Agricultural crops are under severe threats of various biotic and abiotic stresses, including salinity, drought and trace element stress (Adrees et al , Khan et al , Hussain et al , , b, Sytar et al ). Trace element stress is the most prevalent of these stresses, which not only inhibits crop growth by polluting agriculture soils, but also cause diseases in humans and animals (Hu et al , Song et al , Liu et al , Kataria et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Higher ethylene production is due to the peaked expression of ethylene-responsive genes (Sharma et al 2020). Higher production of reactive oxygen species (ROS), induced by some heavy metals, causes oxidative stress (Mittler 2002;Sytar et al 2018). Heavy metals lead to damaging effects such as photochemical reactions, chlorophyll degradation, enzyme inhibition, disruption of membranes integrity, and reduction in metabolic efficiency and carbon fixation (Liu et al 2005;Seregin and Ivanov 2001).…”
Section: Introductionmentioning
confidence: 99%
“…2 C, D). Salicylic acid rose IAA, CK and ABA levels, enhanced cell division in the apical meristem, and improved flowering of the plant (Sytar et al, 2019). In contrast, Alonso-Ramírez et al (2009) reported that there was a cross-talk between SA and GA3 in Arabidopsis thaliana during abiotic stress conditions.…”
Section: Discussionmentioning
confidence: 97%